Exhaust Gas-Superstructure Interactions Onboard Ships with Side Exhaust - Hayati, Abdullah; Arman, Ariffin; Mohammad Yusri, Hassan (ENCON 2013, 2013)
The interference of exhaust gas on the air intake for ventilation system often results in poor Indoor Air Quality (IAQ) on board ships. Low IAQ will adversely affect the performance of human and electronic equipment on board ships and will decrease the performance of the ship's intended capability. Most studies on exhaust gas interference are for ships with the exhaust funnel located on top but current ship design also includes those with side exhaust. This paper presents the results of a study on the interaction between exhaust gas and the ship's superstructure by the determination of the pressure coefficient obtained through wind tunnel testing for ships with side exhaust. A model of an actual ship with side exhaust with a scale of 1:100 was tested in a low speed wind tunnel and pressure coefficients were obtained for various head wind speeds. The results are presented in graphical form and are depicted by the graphs of pressure coefficient versus yaw angle. Preliminary results show that the area around the superstructure near the intake of the ventilation system has low pressure compared to the exhaust discharge. This could lead to the interference of exhaust gas on the intake of the ventilation system and could affect the performance of indoor air quality and electronic equipment on board ships with side exhaust.